Konseling dengan Teknik Demonstrasi untuk Meningkatkan Kemampuan Toilet Training pada Anak - Andri Kusuma Wijaya; Nurhayati Nurhayati; Fatsiwi Nunik Andari; Wenti Dewentri (Malahayati Nursing Journal, 2022)
ABSTRACT: COUNSELING WITH DEMONSTRATION TECHNIQUES TO IMPROVE ABILITY TOILET TRAINING FOR CHILDREN  Abstract: Toilet training is a form of business carried out with the aim of controlling defecation (chapters) and urination (tub) which is carried out in children, this activity is carried out with the hope that children are able to prevent the occurrence of delays in controlling chapters and tubs. Children need to get attention, especially in the elements of growth and development that are carried out from the beginning of child development. So that the formation of children with abilities and qualities with great categories will achieve the future of children with superior categories so as to produce healthy and intelligent children.Objective: The purpose of this study was to determine the effect of demonstration technique counseling to improve toilet training abilities in children. Methods: This research was conducted with a quantitative type of research where the design used was a pre-experimental design using the One Group Pre-Test and Post-Test approaches. Results: The univariate results of this study obtained the characteristics of respondents from 15 respondents, most of the respondents, namely 11 respondents (73.3%) were at the age of 5 years. For the results of the bivariate analysis using the Wilcoxon Signed Ranks Test statistical test, the p value (value) = 0.001 0.05.Conclusion: the conclusion of this study is that there is an effect of counseling with demonstration techniques to improve toilet training abilities in children. Keywords: Counseling, Demonstration, Toilet Training INTISARI: KONSELING DENGAN TEKNIK DEMONSTRASI  UNTUK MENINGKATKAN KEMAMPUAN TOILET TRAINING PADA ANAK Pendahuluan: Toilet training ialah suatu bentuk usaha yang dilakukan dengan tujuan mengontrol buang air besar (bab) dan buang air kecil (bak) yang dilaksanakan pada anak, kegiatan ini dilakukan dengan harapan anak mampu  mencegah terjadinya kondisi keterlambatan mengontrol bab dan bak. Anak perlu mendapatkan perhatian terutama dalam unsur tumbuh kembangnya yang dilakukan sejak awal perkembangan anak. Sehingga akan terbentuknya anak-anak dengan kemampuan dan  kualitas dengan kategori  hebat  sehingga akan tercapainya masa depan anak dengan kategori unggul sehingga menghasilkan anak-anak yang sehat dan cerdas.Tujuan: Tujuan penelitian ini diketahui pengaruh konseling teknik demonstrasi untuk meningkatkan kemampuan toilet training pada anak. Metode: Penelitian ini dilakukan dengan  jenis penelitian kuantitatif dimana desain yang digunakan ialah dengan desain pra eksperimen dengan  menggunakan pendekatan One Group Pre-Test dan Post-Test.  Hasil: Hasil univariat dari penelitian ini didapatkan karakteristik responden dari 15 responden sebagian besar responden yaitu 11 responden (73,3%) berada pada  usia 5 tahun. Untuk hasil analisis bivariat dengan menggunakan uji statistik Wilcoxon Signed Ranks Test  diperoleh nilai p (value) = 0,001 0,05.Kesimpulan: kesimpulan penelitian ini ialah ada pengaruh konseling dengan teknik demonstrasi untuk meningkatkan kemampuan toilet training pada anak. Kata kunci: Konseling, Demonstrasi, Toilet training